Alcohol, tobacco and illicit drug use amongst same-sex attracted women: results from the Western Australian Lesbian and Bisexual Women's Health and Well-Being Survey - McManus Alexandra; Comfort Jude; Hyde Zoë; Brown Graham; Howat Peter (BMC, 2009)
Abstract Background The prevalence of alcohol, tobacco and illicit drug use has been reported to be higher amongst lesbian and bisexual women (LBW) than their heterosexual counterparts. However, few studies have been conducted with this population in Australia and rates that have been reported vary considerably. Methods A self-completed questionnaire exploring a range of health issues was administered to 917 women aged 15-65 years (median 34 years) living in Western Australia, who identified as lesbian or bisexual, or reported having sex with another woman. Participants were recruited from a range of settings, including Perth Pride Festival events (67.0%, n = 615), online (13.2%, n = 121), at gay bars and nightclubs (12.9%, n = 118), and through community groups (6.9%, n = 63). Results were compared against available state and national surveillance data. Results LBW reported consuming alcohol more frequently and in greater quantities than women in the general population. A quarter of LBW (25.7%, n = 236) exceeded national alcohol guidelines by consuming more than four standard drinks on a single occasion, once a week or more. However, only 6.8% (n = 62) described themselves as a heavy drinker, suggesting that exceeding national alcohol guidelines may be a normalised behaviour amongst LBW. Of the 876 women who provided data on tobacco use, 28.1% (n = 246) were smokers, nearly double the rate in the female population as a whole. One third of the sample (33.6%, n = 308) reported use of an illicit drug in the previous six months. The illicit drugs most commonly reported were cannabis (26.4%, n = 242), meth/amphetamine (18.6%, n = 171), and ecstasy (17.9%, n = 164). Injecting drug use was reported by 3.5% (n = 32) of participants. Conclusion LBW appear to use alcohol, tobacco and illicit drugs at higher rates than women generally, indicating that mainstream health promotion messages are not reaching this group or are not perceived as relevant. There is an urgent need for public health practitioners working in the area of substance use to recognise that drug consumption and use patterns of LBW are likely to be different to the wider population and that special considerations and strategies are required to address the unique and complex needs of this population.